MO507ROCK STUDY: RESEARCH STUDY OF CANCER ASSOCIATED KIDNEY DISEASES. (29th May 2021) - Maiorana, Mariarosa; Iannuzzella, Francesco; Giorgi Rossi, Paolo; Ottone, Marta; Gregorini, Mariacristina
Abstract: Background and Aims: The improvement in the survival rates of cancer patients due to the new oncological and biological agents has led to an increase in those who develop kidney diseases. It is now well known that chronic kidney disease (CKD) and cancer are connected in several ways. Nevertheless, although emerging evidence suggests that the risk of renal impairment in cancer patients is high and increasing, the overall incidence and prevalence of CKD in this population are still uncertain. The purpose of the study is to provide data on the prevalence and incidence of CKD in patients included in the Cancer Registry of the province of Reggio Emilia, Italy, since January, 1 st to December, 31 st 2016. Method: single-center, observational and retrospective study. For all patients included, data on sex, age, ethnicity, serum creatinine and related eGFR, type and number of tumors, diagnosis of diabetes mellitus were collected. The main cancer sites considered were breast, colorectal, lung, pancreas, stomach, prostate, lymphomas and leukemias. An eGFR ≥ 60 ml/min1.73m 2 was indicative of a normal kidney function, while an eGFR <60 ml/min/1.73m 2 as kidney impairment. All the eGFR data were calculated not only with the CKD-EPI formula, now recognized as the reference formula for estimating eGFR in the general population, but also with the Wright formula which seems to provide the best estimate in cancer patients. Results: 4254 patients with a cancer diagnosis were identified between January 1 st and December 31 st 2016; of these, 171 patients were excluded due to lack of data. Of the remaining 4083 patients, 776 (19%) had at least an eGFR value <60 mL/min/1.73m 2 prior to cancer diagnosis and 497 patients (11.7%) were identified as affected by CKD. The incidence of new-onset CKD in the following 24 months since cancer diagnosis was 4.4% (186 patients) [95% CI 3.9-5.3] using CKD-EPI formula; using Wright formula, we identified 140 (3.4%) [95% CI 2.9-4.0] new cases of CKD in the same period. For both cohorts of patients (pre-existing CKD and CKD diagnosed after cancer diagnosis), descriptive analyzes were conducted related to demographic and clinical data. Referring to the CKD-EPI formula, in patients with pre-existing CKD (497 patients, 11.7%), the mean age was 81 years (SD ± 8.4), 53.7% were men, 18.3% had a known diagnosis of type 2 diabetes mellitus, 3.6% of these patients had 2 or more cancer diagnosis in the study period. 44.3% were alive at the end of the follow-up (December 31 st, 2018). Using Wright formula, 504 (11.8%) patients with CKD already present at the time of cancer diagnosis were identified; these patients had an average age of 82 years (SD ± 8.4) and in 55.4% of cases were men; 18.8% had type 2 diabetes mellitus and 3.8% had 2 or more cancer diagnosis. Conclusion: The ROCK study is the first large cohort study that allows a clearer estimation of the frequency of CKD in Italian cancer patients. Knowledge of the prevalence of CKD in cancer patients is essential for proper clinical and therapeutic management and implementation of preventive strategies.